(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This paper is the result of a thirty hour seminar on Performance Studies, taught by Dr. Carmela Cutugno at the University of Bologna, as part of a Master course in Theories and Cultures of Representation held by Professor Marco De Marinis. The idea for the chosen topic, as well as part of the readings were suggested during the seminar by Dr. Cutugno, who assisted us for the entire process of thinking and writing about this issues. The seminar was conceived and realized as a performance studies analysis workshop and the final paper was presented and performed as the result of the course. This essay is a synopsis of that work, and its object deals with Pope Benedetto XVI’s resignation, in particular with his transformation from Pope to Emeritus Pope. We investigated such phenomenon through five different perspectives: ethical-psychological, media, theological, moral, economic. Finally, we inserted a survey concerning the reaction that this event has aroused in Brazil.